Identifikasi Kualitas Ruang Terbuka Publik di Landmark Ternate - Gusti Hardyanti Musda; Arinda Wahyuni; Ahmad Nadhil Edar (Universitas Muslim Indonesia, 2022)
Landmark Ternate is one of the largest public open spaces that have an important role as a place for the community to support their activity in the city center of Ternate. However, the presence of public open space in a city is not only intended as a gathering place but also must have a good quality space that can give a particular impression to the visitors of the space. This study aims to identify the quality of public open space Landmark Ternate. This research method is a qualitative approach with descriptive analysis based on data collection results through field surveys and the distribution of online questionnaires to residents who live in the city of Ternate. The variables used to measure the quality of open space are safety, comfort, and enjoyment. The results showed that the existing facilities and people's perceptions were very supportive of the comfort and pleasure factors, while they did not support safety. Thus, it can be seen that the level of comfort and pleasure at Landmark Ternate is good, but not for safety